2005
DOI: 10.1128/iai.73.1.485-493.2005
|View full text |Cite
|
Sign up to set email alerts
|

CXCR3 and Its Ligands Participate in the Host Response toBordetella bronchisepticaInfection of the Mouse Respiratory Tract but Are Not Required for Clearance of Bacteria from the Lung

Abstract: Intranasal inoculation of mice with Bordetella bronchiseptica produces a transient pneumonia that is cleared over several weeks in a process known to require both neutrophils and lymphocytes. In this study, we evaluated the roles of the chemokines MIG (CXCL9), IP-10 (CXCL10), and I-TAC (CXCL11) and their common receptor, CXCR3. Following bacterial inoculation, message expression of interleukin-1 (IL-1), IL-6, and the neutrophil-attracting chemokines KC, LIX, and MIP-2 was rapidly induced, with maximal expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 59 publications
1
37
1
Order By: Relevance
“…Previous investigations have shown that KC (3, 4), MIP-2 (5, 6), lungkine (7,8), and CXCL5 (9) are the most important chemokines to cause neutrophil accumulation in the murine lung. CXCL5 expression was also observed during pulmonary inflammation induced by gram-negative pathogens, Legionella pneumophila (22), Pseudomonas aeruginosa (23), Klebsiella pneumoniae (24), and Bordetella bronchoseptica (25). In the present study, we determined the cellular origin of CXCL5 in lung inflammation.…”
Section: Discussionmentioning
confidence: 81%
“…Previous investigations have shown that KC (3, 4), MIP-2 (5, 6), lungkine (7,8), and CXCL5 (9) are the most important chemokines to cause neutrophil accumulation in the murine lung. CXCL5 expression was also observed during pulmonary inflammation induced by gram-negative pathogens, Legionella pneumophila (22), Pseudomonas aeruginosa (23), Klebsiella pneumoniae (24), and Bordetella bronchoseptica (25). In the present study, we determined the cellular origin of CXCL5 in lung inflammation.…”
Section: Discussionmentioning
confidence: 81%
“…These mice have similar numbers of splenic NK cells at steady state ( [27][28][29], Fig. 6A and data not shown).…”
Section: Nk Cells Enter the Spleen Through The Marginal Zonementioning
confidence: 72%
“…This peak on day 7 after infection correlated with the beginning of reduced colonization of the lower respiratory tract by the TTSS mutant. A recent report by Widney et al (32) showed that the production of IFN-␥ in the lungs of mice infected with B. bronchiseptica peaked 2 days after infection and was not associated with reduced bacterial load. Together with our data, this suggests that that the production of systemic, and not local, IFN-␥ is important for bacterial clearance.…”
Section: Discussionmentioning
confidence: 98%